[that unless the State requires such a process and develops a consistent protocol and approach to investigations as well as requiring follow up that indoor air quality will not be addressed in a manner that will protect Massachusetts workers further] (Tufts Archival Research Center, 2007)
Letter from NEMI to Representative Suzanne M. Bump offering support and comments on the revised indoor air quality bill. States that indoor air quality is a very important factor in the health of workers and that it will take the enforcement of this bill to ensure their safety.